(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the unique features of translation, the theoretical substantiation of its forms, types and their various use by the translator when translating a work, as well as the translator’s own style so as not to violate the original content of the work. translation of the work in this process. In particular, the translation of fantastic works covers not only literary, linguistic, cultural features, but also creates a field terminological environment in the process of their translation. One such work is an indirect translation of Ray Bradbury’s “The Martians Chronicles”.